The Intricate Role of Growth Hormone in Metabolism - Vijayakumar, Archana; Yakar, Shoshana; Leroith, Derek (Frontiers in Endocrinology, 2011)
Growth hormone (GH), a master regulator of somatic growth, also regulates carbohydrate and lipid metabolism via complex interactions with insulin and insulin-like growth factor-1 (IGF-1). Data from human and rodent studies reveal the importance of GH in insulin synthesis and secretion, lipid metabolism and body fat remodeling. In this review, we will summarize the tissue-specific metabolic effects of GH, with emphasis on recent targets identified to mediate these effects. Furthermore, we will discuss what role GH plays in obesity and present possible mechanisms by which this may occur.